2017
DOI: 10.1016/j.jvscit.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm of the external iliac artery is a rare late complication after total hip arthroplasty

Abstract: Vascular injury as a delayed complication of total hip arthroplasty (THA) is rare. We present a case of pseudoaneurysm of the external iliac artery due to chronic irritation from a prominent bone spicule occurring 2 years after revision THA. We successfully managed the patient with open repair, and there has been no sign of recurrence in the 2 years since the previous surgery. This report suggests that patients who have undergone THA should be followed up carefully and assessed for vascular injuries even after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Pseudoaneurysm of the external iliac artery is a well-described complication after THA with several documented case reports and series in the literature [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. The most common proposed causes of these pseudoaneurysms are a malpositioned retractor, migration of acetabular cups, and even migrated cement fragmentation after placement of a cemented femoral stem [ 21 , 24 , 25 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudoaneurysm of the external iliac artery is a well-described complication after THA with several documented case reports and series in the literature [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. The most common proposed causes of these pseudoaneurysms are a malpositioned retractor, migration of acetabular cups, and even migrated cement fragmentation after placement of a cemented femoral stem [ 21 , 24 , 25 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few cases of delayed external iliac artery pseudoaneurysm have been reported. Of the cases reported, most occurred following complications after total hip arthroplasty [ 11 ]. A predisposing factor of this complication is implant infection, which results in the loosening and migration of the acetabular component and damage to external iliac vessels [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proschek et al [23] also reported on a patient who developed common femoral PSA as a result of a malpositioned acetabular screw and presented with a painful groin mass 2 months postoperatively. Fukuhara et al [26] published a case of external iliac PSA 2 years after revision THA, thought to be secondary irritation of the artery by an osteophyte. In their case, the patient presented with thrombosis and acute limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…External iliac artery PSA can also occur from infection [28], [29], [30], [31], [32], [33], [34], [35], acetabular periprosthetic fracture [30], acetabular component migration [27], [30], [31], [32], [33], [36], intrapelvic extravasation of cement [37], prior irradiation [29], and a prominent osteophyte after revision THA [26]. Acetabular screw irritation of the EIA has previously been implicated in the formation of these lesions, but, to our knowledge, this has been universally described in the setting of component migration, and frequently concurrent infection [23], [27].…”
Section: Discussionmentioning
confidence: 99%